Synthesis and Biomedical Applications of Zirconium Nanoparticles: Advanced Leaps and Bounds in the Recent Past. (13th September 2022) - Arshad, Hafiz Muhammad; Shahzad, Amir; Shahid, Sammia; Ali, Sadaqat; Rauf, Abdul; Sharif, Shahzad; Ullah, Muhammad Ehsan; Ullah, Muhammad Inam; Ali, Muhammad; Ahmad, Hafiz Ishfaq
Abstract : Many synthetic routes manufacture zirconium nanoparticles in metal oxide, nitride, and other combination forms. Coupled with other variables such as concentration, pH, and form of precursor used, the various synthetic methods support synthesizing the zirconium metal oxide nanoparticles with changed features. Various synthetic methods were studied, such as sol-gel, hydrothermal, laser ablation, and precipitation. All have different synthetic routes, different precursors and solvents were sued, and the product was characterized by SEM, TEM, photo luminance spectroscopy, UV-absorption spectroscopy, and powder X-ray diffraction. X-ray diffraction determined the crystal structure by identifying the crystal shape, arrangement of atoms, and spacing between them. SEM and TEM studied the particle size and morphology of nanoparticles. UV-visible absorption spectroscopy and PL spectroscopy were used for the determination of optical properties of nanoparticles. Zirconium oxide nanoparticles have many applications in the medical field. The review study primarily focuses on the efficient combination of zirconium dioxide with other additive materials and functionalization techniques used to improve the material's properties, assisting the use of the material in hip arthroplasty and bone tissue applications. The development of sophisticated near-infrared (NIR) absorbing small molecules for useful phototheranostic applications was discussed in this paper.